2012
DOI: 10.1177/1557988312437239
|View full text |Cite
|
Sign up to set email alerts
|

Barbershops as Venues to Assess and Intervene in HIV/STI Risk Among Young, Heterosexual African American Men

Abstract: African Americans, particularly men, are disproportionately affected by the HIV epidemic. Inconsistent condom use and concurrent sexual partnerships are risk factors; there is limited investigation on how these factors influence HIV risk engagement in young, heterosexual, African American men. To identify contextual risk factors that place young men (18-24 years) at risk for HIV infection, one focus group was conducted with 13 men, and questionnaires were administered to 48 men. Participants were 18 to 24 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 44 publications
4
45
0
2
Order By: Relevance
“…Formative research was used to determine the feasibility and appropriateness of implementing an intervention in salons or barbershops, 7,9,10,13,16,1924 assessing customer baseline characteristics, 10,12,17,19,25,26 developing training materials, 8,20 conducting a needs assessment, 27 observing customer–stylist interactions, 28 and assessing stylist–customer relationships. 29 Eight studies used qualitative methods either alone or in combination with a quantitative survey.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Formative research was used to determine the feasibility and appropriateness of implementing an intervention in salons or barbershops, 7,9,10,13,16,1924 assessing customer baseline characteristics, 10,12,17,19,25,26 developing training materials, 8,20 conducting a needs assessment, 27 observing customer–stylist interactions, 28 and assessing stylist–customer relationships. 29 Eight studies used qualitative methods either alone or in combination with a quantitative survey.…”
Section: Resultsmentioning
confidence: 99%
“…7,8,16,21,22,27,28,30 Owners approved of implementing an intervention in their shop, 7,10,16 stylists/barbers were comfortable sharing health messages with customers, 18,19,31 and customers were willing to participate in interventions and receive health information in the salon/barbershop. 10,16,19,21,23 Two feasibility studies trained AA barbers to deliver prostate cancer education to customers. 30,32 Both trainings resulted in a significant increase in barber knowledge of prostate cancer and one found that barber knowledge was maintained after 3 months.…”
Section: Resultsmentioning
confidence: 99%
“…However, there are conceptual gaps in knowledge about risk factors and susceptibility. Participants strongly agreed that culturally appropriate barbershop-based initiatives could have meaningful impact by offering a diabetes self-care and monitoring program [16, 18, 24-27]. Previous research studies have failed to identify a single modifiable risk factor for diabetes in Black communities.…”
Section: Discussionmentioning
confidence: 99%
“…Barbershops are a sort of “country club for Black men” [24]. They are an important channel for health outreach and health promotion targeting Black men [16, 18].…”
Section: Discussionmentioning
confidence: 99%
“…These theoretical frameworks have been used extensively in whole or in part in sexual health research with adolescents, emerging adults, minority and LGBT populations (Hovell et al 1994; Corcoran 2000; Wilson 2008; Baker et al 2012). By combining an individual behaviour change framework with the socio-ecological model, this study approaches HIV risk behaviour as a multilevel challenge, requiring individual, social and structural interventions.…”
Section: Theoretical Frameworkmentioning
confidence: 99%